The Influence of Mental Health on Job Satisfaction: Mediating Effect of Psychological Capital and Social Capital - Cao, Xin; Zhang, Heng; Li, Peng; Huang, Xiaozhi (Frontiers in Public Health, 2022)
Using data from the 2018 Chinese Family Panel Studies (CFPS), based on the mood-congruent theory, this study aims to explore the mechanisms of mental health on job satisfaction from the internal perspective (psychological capital) and external perspective (social capital). The results showed that (1) the two components of mental health have different effects on job satisfaction. The positive component of mental health had a positive effect on job satisfaction, while the negative component of mental health had a negative effect on job satisfaction; (2) Psychological capital and social capital play a mediating role in the relationship between mental health and job satisfaction. (3) After considering the potential endogenous problems between mental health and job satisfaction and conducting additional robustness analysis, including changing dependent variable and changing independent variable, our main results and influence mechanisms are remain robust and reliable. With the emergence of an increasingly competitive knowledge economy era, employees' mental health plays an important role in job satisfaction. Thus, it is imperative for managers to enhance employees' job satisfaction and better implement humanistic management by nurturing employees' psychological and social capital through the mental health.